Pengaruh Surfaktan Biner Cetil Trimetil Amonium Bromida (CTAB)- Hexametilen Triamin (HMT) pada Pembentukan Perak Nanorods menggunakan Katalis Natrium Hidroksida - Atiek Rostika Noviyanti; Iwan Hastiawan; Akrajas Ali Umar; Diana Rakhmawaty Eddy; Gani Abdilah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
Nanoparticles have different physical properties and more interesting than that of bulk material. Nanoparticles are highly preferred for applications in various technologies as a catalyst, the raw material of electronic components, and as an antimicrobial agent. The aim of the research is synthesize of silver nanorods. The effect of a binary surfactant CTAB-HMT on the morphology and homogeneity were investigated using UV/Vis spectrophotometer, TEM, and XRD. Base on the UV/Vis spectra and TEM morphology, silver nanoparticles have two types, spherical and rods shapes. The best product of nanorods was obtained at the composition of CTAB 0.15 M : HMT 0.15 M. The structure of nanorods obtained were face center cubic (fcc).